Controlled transparency and wettability of large-area nanoporous anodized alumina on glass. (15th July 2015) - Lee, Seungwoo; Kim, Wook; Lee, Sangmin; Shim, Sangdeok; Choi, Dukhyun
Abstract : Here, we investigate the morphological and optical properties of nanoporous anodized alumina (NAA) on a glass wafer for anodizing times from 60 to 120 s and widening times from 0 to 80 min. Furthermore, we explore the corresponding wetting properties. Finally, we demonstrate a highly transparent superhydrophobic surface by using organic molecule-treated NAA on glass. Successful development of large-area NAA with tunable transparency and wettability opens up opportunities for self-cleaning and anti-frost glass for use on skyscrapers or in vehicles.